2006
DOI: 10.1001/archotol.132.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma

Abstract: Patients: Fifty consecutive patients diagnosed as having esthesioneuroblastoma were treated with a standardized protocol during a 28-year period. Patients with tumors staged Kadish A or B received preoperative radiotherapy followed by craniofacial resection, while patients with Kadish stage C disease were treated with preoperative sequential chemotherapy and radiotherapy followed by a craniofacial resection. The mean follow-up is 93 months (range, 1-330 months). Results:The disease-free survival was 86.5% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…In a study reported by a group from the University of Virginia, patients with Kadish stage C received preoperative sequential chemotherapy (two cycles of vincristine + cyclophosphamide ± doxorubicin) and radiation therapy, followed by craniofacial resection. The 5-and 15-years survival rates reported for this group were 72% and 60%, respectively [12] , which are similar to other values reported without the use of chemotherapy [3,10] . There is limited experience in the metastatic setting owing to the rarity of this subset of patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In a study reported by a group from the University of Virginia, patients with Kadish stage C received preoperative sequential chemotherapy (two cycles of vincristine + cyclophosphamide ± doxorubicin) and radiation therapy, followed by craniofacial resection. The 5-and 15-years survival rates reported for this group were 72% and 60%, respectively [12] , which are similar to other values reported without the use of chemotherapy [3,10] . There is limited experience in the metastatic setting owing to the rarity of this subset of patients.…”
Section: Discussionsupporting
confidence: 88%
“…The most frequent clinical manifestations are nasal obstruction (70%), epistaxis (46%), rhinorrhea, and headache. Anosmia, otalgia, and ocular pain are often present due to the neoplasm's invasion to adjacent structures [2,3,11,12] . During its growth, it extends to the skull base and can spread to the brain or spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a median follow up time of 82.3 months, patients with ENB can experience disease recurrence even 10-years after completion of their initial treatment. 4, 2022 As such, while we observed a trend towards improved neck control with ENI, this difference may become significant with longer follow-up. Unfortunately, overcoming the aforementioned limitations is difficult given the rarity and natural history of ENB.…”
Section: Discussionmentioning
confidence: 52%
“…Due to concern of late effects in children, doses in the range of 54 – 59.4 Gy are recommended [19]. In some adult series, doses as low as 50 Gy have been used without compromising outcomes [20]. Though some authors recommend prophylactic neck irradiation even in patients without cervical node involvement, this is controversial [16, 18].…”
Section: Discussionmentioning
confidence: 99%